Edukasi Hukum Keluarga Islam Berbasis Digital Melalui Instagram pada Akun @Familylawnesia - Muhammad Arief Ridha Rosyadi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
This article examines Islamic Family Law education on the Instagram social media space on the @familylawnesia account initiated by Rahmatullah since February 2021. Currently, this account is the most popular Islamic Family Law education account on Instagram. This research is qualitative with library research and then analyzed using qualitative descriptive methods and content analysis based on data from the @familylawnesia account and several sources of documentation related to Islamic education. This data was analyzed based on literature relevant to this research topic. The results of this study indicate that digital-based Islamic family law education on the Instagram account @familylawnesia is carried out by displaying content about Islamic family law that is not limited to conceptual theoretical Islamic family law, but rather dynamic discussion, up to date material and objects of study in issues of Islamic family law from classical to contemporary (present). Thus, making the @familylawnesia account education communication approach more adaptable and felt appropriate in responding to the era of disruption with the industrial revolution 4.0 and the generations that participated in its development. Keywords: Islamic Family Law, Instagram, Disruption and Industrial Revolution